2019
DOI: 10.1002/jsfa.9878
|View full text |Cite
|
Sign up to set email alerts
|

Fruits of wild and semi‐domesticated Diospyros tree species have contrasting phenological, metabolic, and antioxidant activity profiles

Abstract: BACKGROUND In contrast to commercial Diospyros species, Mesoamerican fruit‐producing species are scarcely known, particularly wild species that might harbor desirable traits suitable for breeding. Thus, metabolomic, chemical, and antioxidant profiles of fruits harvested from cultivated Diospyros digyna and wild Diospyros rekoi trees during consecutive winter seasons were obtained. Fruits were harvested in habitats having marked differences in soil quality, climate, and luminosity. RESULTS D. digyna fruits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…This study represents part of an ongoing investigation to determine the influence that domestication, seasonality, growing habitat, and cultural practices, or the lack thereof, have on the physiology and metabolism of two Mesoamerican Diospyros species: D. digyna and D. rekoi . Similar to previous reports describing significant differences in tree physiology [15] and fruit physicochemical properties [16], the present investigation revealed that metabolic abundance and diversity was greater in leaves of wild D. rekoi trees compared to those of domesticated D. digyna . This finding suggests that the domestication process in D. digyna reduced the metabolic richness of their leaves without affecting important nutraceutical traits, such as antioxidant capacity.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study represents part of an ongoing investigation to determine the influence that domestication, seasonality, growing habitat, and cultural practices, or the lack thereof, have on the physiology and metabolism of two Mesoamerican Diospyros species: D. digyna and D. rekoi . Similar to previous reports describing significant differences in tree physiology [15] and fruit physicochemical properties [16], the present investigation revealed that metabolic abundance and diversity was greater in leaves of wild D. rekoi trees compared to those of domesticated D. digyna . This finding suggests that the domestication process in D. digyna reduced the metabolic richness of their leaves without affecting important nutraceutical traits, such as antioxidant capacity.…”
Section: Introductionsupporting
confidence: 90%
“…Although less evident, a certain degree of leaf metabolic variability in the trees sampled was also observed. A previous study implied that domestication of D. digyna led to the production of larger and more symmetrical fruits, in addition to a divergence from D. rekoi fruits in several other physicochemical properties [16]. This concept was supported by the decreased metabolic diversity and seasonal variability in the chemistry of D. digyna leaves herein reported.…”
Section: Discussionsupporting
confidence: 65%
“…There have been no reports about the content of pectin, but its presence has been reported, which is useful in the preparation of products based on black sapote. 39,40 Proteins (1 g/100 g of pulp) 38 and fat (1.2 g/100 g of pulp) 41 have also been reported in the pulp.…”
Section: ■ Descriptionmentioning
confidence: 97%
“…Biological compounds that show antioxidant activity have been identified. The large amount of phenolic compounds shows an antioxidant activity similar to that of guava and papaya; 34 however, the variability in antioxidant activity might be due to the harvest season 38 and maturation of the fruit. 33,39,44 The type of solvent used for the extraction also may affect the antioxidant activity values; it increases when an extraction is carried out with a hydrophilic solvent compared to a lipophilic one.…”
Section: ■ Bioactive Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation